Resonansi Pesan Storyteling Iklan dalam Komunikasi Humor - Muhammad Irfan Mubarok; Rohimah, Afifatur (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2026)
This study examines humorous communication in YouTube advertising storytelling through the Head & Shoulders version featuring Joe Taslim. The primary objective is to elucidate the construction of humorous elements and the formation of message resonance among audiences. A qualitative descriptive approach employing Roland Barthes' semiotic analysis is utilized to uncover the denotative, connotative, and mythic meanings embedded in the advertisement. The findings reveal that humor is constructed via situational hyperbole, character contrast, and narrative surprise, which effectively enhance audience engagement and strengthen brand recall. Message resonance emerges through cultural proximity, representations of masculinity, and relevance to everyday audience experiences. The contribution of this study lies in explaining how humor-based storytelling strategies in digital advertising build message resonance not only through symbolic meanings but also via emotional connections with audiences. These insights enrich the literature on digital advertising communication by highlighting the role of humor as an effective rhetorical strategy in fostering audience attachment and bolstering brand message effectiveness on digital platforms.